Incorporação de diclofenaco de sódio em fibras de poli etilcelulose eletrofiadas para liberação controlada para aplicação em adesivos transdérmicos - Silva, Daiany Helscher da (2022)
The increase in the use of medicines has generated great impacts on the human body, not always positive. Among them, we can mention some adverse reactions, such as allergy, toxicity, liver damage caused by prolonged use of drugs. In the last 5 years, more than 46,000 articles were published involving drugs and polymers according to the CAPES Periodicals Portal, with the aim of reducing the negative effects, adequately controlling the amount applied to the patient, increasing the contact time between the drug and the dermis, reducing its toxicity and minimizing pollution to the environment, due to the low amount of the drug exposed to the living organism. In this perspective, this article applied electrospinning for the production of nano/microwires of poly ethyl cellulose with the incorporation of the drug (sodium diclofenac) and study of drug release in aqueous medium. The membrane obtained was characterized by FTIR, SEM and DSC techniques. For the release study, a complete factorial design was performed in duplicate, where the release time, temperature, drug concentration incorporated in the fiber and the ionic strength of the medium were changed. According to the results obtained, the first three variables caused an increase in drug release and the effect of ionic strength caused a reduction. A Higuchi release model was applied and a constant of 2.82 ± 0.06x10-5 min.0.5 was obtained for a solution with a temperature of 35 °C, distilled water and a drug concentration of 5% (best release conditions). It is concluded that the system can be applied in transdermal dressings, however, the effect of ionic strength cannot be disregarded as it has a negative effect on the amount released.